2009
DOI: 10.1111/j.1754-9485.2009.02097.x
|View full text |Cite
|
Sign up to set email alerts
|

Centre credentialing for Trans Tasman Radiation Oncology Group trial 06.02: multicentre feasibility study of accelerated partial breast irradiation

Abstract: Given the impact of contouring on dose distributions, quality assurance procedures in clinical trials of PBI need to take into account both the technical approaches and the contouring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…This indicates that patients should not be excluded for PBI on the basis of PBI breast volume ratio. Patients may also still be eligible for PBI if the seroma is larger than 2 cm, which has been used as selection criteria in recent clinical trials 14,30,32 and < 3 cm as per international consensus statements and guidelines. 5,6,13 Our study reported a 21% incidence of UIQ targets for the imaging study and 26% for the positioning component, which is higher than the 16% reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that patients should not be excluded for PBI on the basis of PBI breast volume ratio. Patients may also still be eligible for PBI if the seroma is larger than 2 cm, which has been used as selection criteria in recent clinical trials 14,30,32 and < 3 cm as per international consensus statements and guidelines. 5,6,13 Our study reported a 21% incidence of UIQ targets for the imaging study and 26% for the positioning component, which is higher than the 16% reported elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…The following structures were contoured for each case by a single individual (AS) to reduce intra‐operator variability: 24 …”
Section: Methodsmentioning
confidence: 99%
“…The following structures were contoured for each case by a single individual (AS) to reduce intra-operator variability: 24 1 The clinical target volume (CTV) was the ipsilateral whole breast as determined clinically and included all glandular breast tissues evident on the planning CT scans. The CTV was defined superiorly at the inferior edge of the clavicular head, inferiorly at the inframammary fold, medially at the ipsilateral sternal edge and laterally to include all apparent breast tissues.…”
Section: Target Volumes and Organs At Riskmentioning
confidence: 99%
“…These techniques which exceed convention may be introduced safely in the context of multicenter feasibility studies. [1113]…”
Section: Introductionmentioning
confidence: 99%